Estrategias metodológicas para la enseñanza de electromecánica y su contribución al rendimiento académico de los estudiantes de la Unidad Educativa Laurel cantón Daule, provincia Guayas - Bodero Hidalgo, Bayron Manuel (2017)
The continuous academic preparation of the teaching staff, on the methods of teaching and learning, will allow them to help to improve the intellectual capacities of the students in the classroom and mainly within the practical workshops of automotive electromechanics, therefore, the continuous training they are a predisposing factor for the growth of the academic performance of the students. The main objective of this project was to establish one or more strategic teaching-learning models to improve the academic performance of students within the automotive electromechanics workshops of the Laurel Educational Unit, Daule canton, Guayas province. For the realization of the present final report we worked with a sample of 90 students, which according to the evaluation of the applied methodology 32.22% (29) mentioned to be neither in agreement nor in disagreement. Regarding the evaluation of information provided by the teacher to the students, 37.78% (34) said they agreed with the information provided. According to the level of clarity of the objectives and contents developed in the study program, 34.44% (31) is in agreement with the information provided by the teachers, likewise 41.11% (37) agreed with the information provided by teachers, which is prepared, clear and understandable. 46,67% (42) mentioned that the teacher motivates participation in the classroom constantly. Regarding the teacher evaluation system, 34.44% (31) agreed with the evaluation system applied. In response to the implementation of resources in automotive electromechanics workshops, 46.67% (42) said they agreed with the implementation of the resources since it has allowed them to improve their academic performance. Finally, 60.00% (54) students mentioned to agree that the teacher must be continuously trained, for the improvement of the education in the students.